On the Lady Chapel in Chester Cathedral - Blomfield, George Becher, 1801-1885 (Salt Lake City, UT : Project Gutenberg, 2020)
"On the Lady Chapel in Chester Cathedral" by George Becher Blomfield is a scholarly paper written in the mid-19th century. This work is an architectural study that delves into the history and features of the Lady Chapel located within Chester Cathedral. It serves as a detailed account of the chapel's architectural significance and its historical relevance, particularly regarding the veneration of the Virgin Mary and its evolution through time. In the paper, Blomfield discusses the architectural elements of the Lady Chapel, its construction around the late 13th century, and its symbolic representations, particularly in relation to the Virgin Mary and the martyrdom of St. Thomas Becket. He highlights various features of the chapel, including the groined roof adorned with large bosses, the historical modifications made over the centuries, and its role during significant events such as the Reformation. Furthermore, the text reflects on past renovations, the artistic intentions behind the restoration efforts, and the importance of preserving the chapel's original character in light of evolving architectural practices. (This is an automatically generated summary.)
Release date is 2020-04-25
Transcribed from the 1859 Courant Office edition by David Price
Keywords: Chester Cathedral; Lady Chapel (Chester Cathedral); Church architecture -- England -- Chester; Sacrament chapels; Chester (England) -- Antiquities